Notes on the typification of the names Utricularia bremii Heer and U. intermedia Dreves & Hayne (Lentibulariaceae) - Astuti, Giovanni; Peruzzi, Lorenzo (Phytotaxa, 2018)
In the framework of a systematic revision of Central European Utricularia L. (Astuti & Peruzzi 2018), we came across a first-step typification (Meister 1900) concerning the name Utricularia bremii Heer in Koelliker (1839: 142), and a name yet untypified, i.e. U. intermedia Dreves & Hayne (1798: 104). A second-step typification and a lectotypification are designated here, respectively.